Validation of the metacognitive skills questionnaire for drivers of vehicles (CHMC) - Antoñanzas, Jose Luis; Salavera, Carlos (Frontiers in Psychology, 2023)
Knowing what strategies users use in the difficult task of driving has always been a priority objective in road safety, given that road accidents are one of the main causes of death in the world, as confirmed by the WHO. In this sense, the metacognitive skills questionnaire for drivers was validated. The questionnaire measures the metacongitive skills used by vehicle drivers at three times before, during and after driving. The results of both the exploratory factor analysis (.92 alpha by Cronbach) and the confirmatory factor analysis show the existence of three factors, a planning factor, a self-realization factor and a third evaluation factor. Finding these results together with a psychoeducational intervention design, will improve the behavior of drivers and in turn will serve to improve the training programs of the same to the different institutions and centers responsible for such training.